Evaluating learning of medical students through recorded lectures in clinical courses. Issue 7 (July 2021) - Orellano, Carlos; Carcamo, Cesar
Abstract: One solution offered by technology is learning through recorded lectures (RLs). The main objective of the study was to evaluate the efficacy of online RLs in learning of clinical courses at a School of Medicine. The study comprised four phases: (i) pre-post uncontrolled study to evaluate knowledge gain with RLs, (ii) non-randomised crossover study to compare learning with RL before or after a face-to-face lecture (FL), (iii) focus groups to evaluate perceptions from students about RLs and, (iv) randomised controlled trial to verify whether the addition of questions every 10 min and a summary webpage to an RL improve knowledge. Results showed that knowledge gain occurred through RLs and was similar to FLs. Additionally, either watching an RL after attending an FL or vice versa showed comparable additional knowledge gain. Furthermore, students were in favour of the use of RLs but not as a replacement of FLs. At last, the insertion of questions and a summary in RLs meant no additional knowledge gain. In conclusion, it is feasible to learn through RLs in clinical courses, but the importance given to FLs suggests adopting blended learning. Abstract : Undergraduate medical education; Online systems; eLearning; Recorded lectures.